MEDIA POP-UP BERBASIS KEARIFAN LOKAL : PENDEKATAN KREATIF DALAM PEMBELAJARAN IPAS MATERI INDONESIA KU KAYA BUDAYA INDONESIA DI SD - Shafiyyah, Shafiyyah; Alfina, Rizka; Ningsih, Tri Widia; sabaryati, Johri (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
Pop-up book media is designed as a local creative approach to integrate local cultural elements into teaching, thereby increasing students' interest and understanding of the subject matter. The aim of this study is to develop a pop-up book learning medium based on local wisdom in science subject with the material